FASE DAN METODE RECOVERY - Wahyana Mujari Wahid; Arimbi MB; Abdul Rahman (Program Studi Ilmu Keolahragaan, 2022)
Competitive sport is a sport that requires every athlete, both in training and in competitions, to bring out all of his abilities, the impact of which will certainly cause physical and mental fatigue which will cause various negative impacts if the situation is left unchecked, including a decrease in performance which will lead to a decrease in achievement. Therefore, after doing exercises or matches, recovery should be done. This recovery phase is very much needed by the body to restore the body to its initial state before exercising or competing. The provision of knowledge about the importance of recovery aims to enable administrators, managers, coaches and athletes to know, design and choose the right recovery method and time to restore the athlete's best performance after training or competition. The problem faced by partners in this Community Partnership Program (PKM) is the lack of knowledge about the importance of phases and recovery. How is the threat of overtraining when the recovery phase is less than optimal and what recovery methods can accelerate the process of recovering from fatigue for an athlete. The solution that can be given to partners is to provide socialization and training on the importance of recovery phases and methods. With the increase in partner knowledge, it is hoped that in the future partners can apply the recovery phase and recovery methods well so that athletes can show their best performance in every practice and match. Partners who are sports administrators, managers, coaches and athletes under the guidance and collaboration of P3KORIN feel directly the benefits of this socialization and training. Partners feel that these recovery phases and methods are very important for sports players to know because the phase and selection of a good recovery method is one of the keys for athletes to continue to perform in their best performance, both in training and in competitions.